2022
DOI: 10.3390/molecules27217183
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Induces the Apoptosis of Prostate Cancer Cells via ROS-Mediated HIF-1α Expression

Abstract: Prostate cancer (PCa) is the most common malignancy to endanger the health of male genitourinary system. Clinically, paclitaxel (PTX) (C47H51NO14), a diterpene alkaloid, is commonly used as an effective natural antineoplastic drug during the treatment of PCa. However, the mechanism and pathway involved in the function of PTX are poorly understood. In the current study, we employed the CCK-8 assay, revealing that PTX can inhibit the survival and induce the apoptosis of PC3M cells (a human prostate cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Disturbance of microtubule polymerization by paclitaxel renders Rac1 stabilization in the active NOX complex, leading to increased ROS generation 7 . Further, it has also been reported that paclitaxel induces the apoptosis of prostate cancer cells via ROS‐mediated hypoxia‐inducible factor‐1α expression 52 . As the auranofin treatment inhibits the cellular redox system, it will synergistically improve paclitaxel‐induced ROS generation in the breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbance of microtubule polymerization by paclitaxel renders Rac1 stabilization in the active NOX complex, leading to increased ROS generation 7 . Further, it has also been reported that paclitaxel induces the apoptosis of prostate cancer cells via ROS‐mediated hypoxia‐inducible factor‐1α expression 52 . As the auranofin treatment inhibits the cellular redox system, it will synergistically improve paclitaxel‐induced ROS generation in the breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…7 Further, it has also been reported that paclitaxel induces the apoptosis of prostate cancer cells via ROS-mediated hypoxia-inducible factor-1α expression. 52 As the auranofin treatment inhibits the cellular redox system, it will synergistically improve paclitaxel-induced ROS generation in the breast cancer cells. DRG cells.…”
Section: Disturbance Of Microtubule Polymerization By Paclitaxel Rendersmentioning
confidence: 99%
“…Next, we attempted to examine the mechanism by which deguelin inhibits paclitaxel resistance in SKOV3-TR cells. Several reports indicated that the mechanism of cell death caused by paclitaxel treatment may be due to excessive 18,78 To determine whether ROS mediates the cell cytotoxicity in SKOV3-TR cells cotreated with deguelin and paclitaxel, we additionally treated NAC and then examined cell viability by WST-1 analysis. Figure 5A showed that NAC did not inhibit cell cytotoxicity induced by cotreatment with deguelin and paclitaxel in SKOV3-TR cells.…”
Section: Deguelin Suppressed the Expression Of Bcl-2 And Mcl-1 And Th...mentioning
confidence: 99%
“…This prevents the disassembly of microtubules and consequently induces mitotic arrest, which in turn induces cell death [ 157 ]. ROS induction has been suggested as a secondary/alternative mechanism of action of paclitaxel and has been reported in osteosarcoma [ 158 ], prostate cancer [ 159 ], and non-small-cell lung cancer [ 160 ] cells. However, of these studies, only one reported that the use of the ROS scavenger N-acetylcysteine abrogated paclitaxel-mediated effects [ 159 ].…”
Section: Pro-oxidative Drugs In the Clinical Settingmentioning
confidence: 99%
“…ROS induction has been suggested as a secondary/alternative mechanism of action of paclitaxel and has been reported in osteosarcoma [ 158 ], prostate cancer [ 159 ], and non-small-cell lung cancer [ 160 ] cells. However, of these studies, only one reported that the use of the ROS scavenger N-acetylcysteine abrogated paclitaxel-mediated effects [ 159 ]. Moreover, it has only recently been clarified that mitochondrial accumulation, a consequence of paclitaxel-induced mitotic arrest, causes mitochondrial oxidative stress [ 161 ].…”
Section: Pro-oxidative Drugs In the Clinical Settingmentioning
confidence: 99%